An experimental study of forced convection effectiveness of Al2O3-water nanofluid flowing in circular tubes. (April 2017) - Ho, C.J.; Chang, C.Y.; Yan, Wei-Mon
Abstract: In the present study, experimental efforts have been performed to explore the forced convection heat transfer using water-based suspension of Al2 O3 nanoparticles (nanofluid) to replace the pure water as the working fluids in circular tubes. The nanofluid was prepared as a functional forced convection fluid and the thermal properties including the density, thermal conductivity, and dynamic viscosity were investigated experimentally. Besides, forced convection heat transfer in circular tubes was investigated with water-based nanofluid containing various mass fractions of the Al2 O3 nanoparticles (2, 5, and 10 wt%) under the following operating conditions: the volume flow rate Q f  = 23.6–183.5 cm 3 /min (the Reynolds number Re f, 0  = 188–2095), the heating power applied at the outer wall of the tube q o  ,   eff . ″  = 1908–7362 W/m 2, and the inlet fluid temperature T in  = 24.5–25.5 °C or 49.5–50.5 °C. Measured data showed that the dispersion of increasing mass fraction of Al2 O3 nanoparticles can effectively improve the thermal conductivity relative to the pure water. Besides, higher average heat transfer effectiveness ε − h, btd and figure of merit FOM are noted for the cases with higher inlet fluid temperature T in .